Empowering IoT: leveraging data sensor communication with LoRAWAN in diverse environments - Noprianto Noprianto; Habibie Ed Dien; Septian Enggar Sukmana; Fayyadh Al Baity; Mustika Mentari (Acta Polytechnica)
The Internet of Things (IoT) connects countless devices, such as sensors and actuators, necessitating an efficient long-range communication technology. Low Power Wide Area Network (LPWAN) solutions, such as LoRAWAN, SIGFOX, and NB-IoT, address this demand. LoRAWAN, known for its low power consumption, excels in Line of Sight (LOS) conditions, offering an effective long-range wireless communication. It’s ideal for monitoring open areas. In Non-Line of Sight (NLOS) scenarios, LoRAWAN provides wide coverage and energy efficiency, though the signal quality may slightly decline. This research tests LoRAWAN’s performance for sensor data communication both inside multi-story buildings (up to 8 storeys) and outside. The results show successful data transmission in both scenarios, including up to 2.60 km with a 35 dBi outdoor antenna.